Tiktok Business Analysis and Media Marketing Strategy: SWOT and PESTLE Approach - Hilzam Saiga Hamas; Cantika Dwi Fransiska; Umi Tasyania Apriliani; Buana Madu Hayati; Achmad Kautsar (International Journal of Social, Economic, and Business, 2024)
TikTok, or known as Douyin in China, is a social media platform that provides short videos and has gained widespread popularity throughout the world, especially among the younger generation. The impact needs to be discussed further by explaining the SWOT and PESTLE analysis to analyze TikTok's internal and external weaknesses and strengths. By combining SWOT and PESTLE analysis, a project or organization can have a better understanding of the situation and environmental conditions in which they operate, so they can develop strategies that are more effective and successful in achieving their goals. This research method is descriptive qualitative by observing and analyzing secondary data. PESTEL analysis provides insight into how external factors, such as shifts in government policies related to social media and evolving cultural trends, may affect TikTok’s operations and expansion across different markets.